2020
DOI: 10.1155/2020/1421853
|View full text |Cite
|
Sign up to set email alerts
|

Dendrobium officinale Flower Extraction Mitigates Alcohol‐Induced Liver Injury in Mice: Role of Antisteatosis, Antioxidative, and Anti‐Inflammatory

Abstract: The study aimed to evaluate the protective effect of Dendrobium officinale flower extraction (DOFE) on alcohol-induced liver injury and its probable mechanisms in mice. The chemical composition of DOFE was performed via UPLC/MS. Male Kunming mice were used to establish alcohol-induced liver injury models by oral gavage of 56% alcohol. Results showed that DOFE dramatically attenuated the increased serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total cholesterol (TC), and triac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…In recent years, a variety of TCM prescriptions for the treatment of liver diseases have been widely studied, such as Huangqi and Xiaochaihu decoctions ( Zhang et al, 2017 ; Zhao et al, 2017 ; Xi et al, 2018 ). In addition, there are many TCM extracts, such as ethanol precipitate (polysaccharide) hepatoprotective, that have received some researchers’ attention ( Wu et al, 2011 , 2020 ; Yuan et al, 2018 ). In this study, the hepatoprotective effects of the water extract (MRGD) and ethanol precipitation extract (MRGDE) were compared.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a variety of TCM prescriptions for the treatment of liver diseases have been widely studied, such as Huangqi and Xiaochaihu decoctions ( Zhang et al, 2017 ; Zhao et al, 2017 ; Xi et al, 2018 ). In addition, there are many TCM extracts, such as ethanol precipitate (polysaccharide) hepatoprotective, that have received some researchers’ attention ( Wu et al, 2011 , 2020 ; Yuan et al, 2018 ). In this study, the hepatoprotective effects of the water extract (MRGD) and ethanol precipitation extract (MRGDE) were compared.…”
Section: Discussionmentioning
confidence: 99%
“…One study has demonstrated that the treatment with D. officinale ethanol extracts at the doses of 4.375 and 17.5 mg/kg for 9 weeks prevented liver and kidney damage in hyperuricemic rats by suppressing the protein levels of NF-κB and TLR4 compared with the model group (0.15% adenine, 10% yeast extract, and 89.85% standard diet) (Lou et al, 2020). Likewise, another study revealed that D. officinale flower water extracts (50, 100, 150, and 200 mg/kg) showed protective effects on alcohol-induced (10 ml/kg) liver injury by its anti-steatosis, anti-oxidative, and anti-inflammatory effects (Wu et al, 2020). However, additional evidence from randomized controlled trials is required to identify other regulatory mechanisms that may be responsible for the protective effects on liver and kidney.…”
Section: Protective Effects On Liver and Kidneymentioning
confidence: 94%
“…The retention time (Rt), molecular formula, and ion and ions after fragmentation are shown in Table 1. The Rt and fragmentation information of compounds 13,14,16,17,19,20,23,24, and 25 were compared with those of standards. The major constituents of DOF-W were flavonoids (Figure 8).…”
Section: Determination Of Phytochemicals Using Uplc-q/tof-ms/msmentioning
confidence: 99%
“…However, as a medicinal by-product, the flowers of D. officinale are typically discarded and rarely studied. Recently, the flowers of D. officinale have been reported to be rich in nutrients and other chemical ingredients, including anthocyanins, flavonoids, and polysaccharides, and specific bioactivities have been elucidated, such as liver protection as well as hypoglycaemic, antioxidant, and antihypertensive effects (16)(17)(18). Therefore, it is necessary to establish reliable methods for component analysis of D. officinale flowers and expand its use for health-related products through comparison with stems.…”
Section: Introductionmentioning
confidence: 99%